Validity and reliability study of Effects of Digital Games in Early Ages Scale - BALABAN DAĞAL, ASUDE (PEGEM AKAD YAYINCILIK EGITIM DANISMANLIK HIZMETLERI TIC LTD STI, 2019)
The aim of this research is to develop a scale aiming to measure the effects of digital games on children during early childhood period according to parent perceptions. In the course of developing the scale items, related literature was reviewed in detail and relevant scales and the previous research carried out were examined. After the expert opinions were obtained, the scale was sent to the families of 1500 children by administrators and teachers who worked in the primary schools and kindergartens, which were randomly selected and were affiliated to the Provincial Directorate of National Education of Istanbul. 731 data were included in the survey. 342 girls and 389 boys aged between 55-95 months constituted the sample of the research. The data regarding the children were gathered by means of forms filled out by their parents. In order to determine the construct validity of the scale, exploratory factor analysis, which is one of the principal component analyses, was applied. As a result of the analysis, the KMO value was found as .90. The total variance explained is 63.40%. Factor load values were found to be ranging from .87 to .54. The internal consistency coefficient of the total scale was found to be .91. Internal consistency coefficients of the factors were .82 for entertainment, .90 for learning, .86 for physical, .87 for social dimension and .84 for emotional dimension. Analyses showed that the Effects of Digital Games in Early Ages Scale which is a scale of 25 items, is a valid and reliable scale.
Keywords: Early childhood; Digital games; Scale development; VIDEO GAMES; COMPUTER; SCHOOL; EDUCATION; HOME